Ḥall mushkilāt Kitāb al-ishārāt wal-tanbīhāt : Mashhūr bih Sharḥ-i Ishārāt - Ṭūsī, Naṣīr al-Dīn, (Miras Maktoob, ISBN: 9789004365452., 2019)
Naṣīr al-Dīn Ṭūsī (d. 672/1274) was an influential philosopher, theologian, mathematician and astronomer, besides being the first director of the famous observatory at Marāghah near Tabriz as well as a man of politics. Author of a large number of scholarly works, he is especially famous for such treatises as his Tajrīd al-iʿtiqād on theology, the Zīj-i Īlkhānī on astronomy, and his Akhlāq-i Nāṣirī on ethics. The present volume contains a facsimile edition of an ancient copy of another famous work by him, the Ḥall mushkilāt al-Ishārāt , which is his influential commentary on Avicenna's (d. 428/1037) groundbreaking Kitāb al-ishārāt wal-tanbīhāt . The Ishārāt is commonly regarded as Avicenna's final statement on all there is to know in logic and philosophy. Directed at a restricted readership of trusted specialists, it was deliberately written in a terse, impenetrable style. From the many commentaries that were written on it, the one by Ṭūsī would be decisive for the later Avicennan tradition.